Acute stroke in patients on new direct oral anticoagulants: how to manage, how to treat? - Epple, Corina; Steiner, Thorsten (Expert opinion on pharmacotherapy, 2014)
Introduction: For a long time, vitamin K antagonists (VKA) were the only available oral anticoagulants for clinical use. It is conceivable that the number of patients treated with novel direct oral anticoagulants (NOAC) will increase, due to the easy handling and the favorable risk-benefit profile compared with VKA. It is, therefore, expected that clinicians will be increasingly confronted with the question on how to treat acute ischemic stroke (AIS) if there is an indication for thrombolysis or how to manage intracranial bleedings.Areas covered: In this review, we discuss controversies on thrombolysis in patients anticoagulated with NOAC, the dilemma of when to restart anticoagulation after AIS, and whether (and when) to re-institute oral anticoagulation after a brain hemorrhage. We provide suggestions for the management of these situations.Expert opinion: Thrombolysis for patients with ischemic stroke who were given warfarin at subtherapeutic International normalized ratio values (≤ 1.7) may be considered according to guideline. Thrombolysis is contraindicated if intake of NOAC is reported in a patient, but no other information is available on-time of last intake of NOAC. Prothrombin complex concentrate have been proposed as a plausible, but unproven therapy to reverse the anticoagulant effects of NOACs.